2012
DOI: 10.1089/jwh.2012.3528
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Nutritional Status and Antenatal Depressive Symptoms in African American Women

Abstract: African American women with lower VDN exhibit increased depressive symptoms. Research on vitamin D supplementation for reducing antenatal depressive symptoms is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
92
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(94 citation statements)
references
References 50 publications
0
92
2
Order By: Relevance
“…Notably, Cassidy-Bushrow, et al also found history of depression to have a minimal effect on their estimates. 22 Some limitations of our study deserve mention. First, our study, which is moderate in size, may not be powered to assess statistically significant associations.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…Notably, Cassidy-Bushrow, et al also found history of depression to have a minimal effect on their estimates. 22 Some limitations of our study deserve mention. First, our study, which is moderate in size, may not be powered to assess statistically significant associations.…”
Section: Discussionmentioning
confidence: 89%
“…22,23 In a study conducted (Table 2). However, among women reporting no LTPA during pregnancy, the associations were stronger and statistically significant.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Vitamin D deficiency and inadequacy are common during pregnancy, especially among African-American women (Johnson et al, 2011;Cassidy-Bushrow et al, 2012a;Nassar et al, 2011) and African-American women also appear to be at a higher risk of altered inflammatory responses (Ness et al, 2004;Van Dyke et al, 2009). Therefore, we sought to explore the association between early-pregnancy VDN as assessed by serum 25-hydroxyvitamin D, the best available measure of overall VDN status and the most clinically useful, and mid-pregnancy biomarkers of inflammation, specifically in African-American women.…”
Section: Introductionmentioning
confidence: 99%